HUBUNGAN POLA ASUH DAN ASUPAN MAKANAN DENGAN STATUS GIZI BALITA - Fitri Puspita Sari (NHM PRESS, 2023)
Nutrition has an important role in human life, so we must be able to understand the nutritional needs of mothers and children and efforts to fulfill them as an effort to create optimal levels of maternal and child health. This research is an analytic study with a cross-sectional design, to determine the relationship between parenting style and food intake with the nutritional status of toddlers in the work area in primary Health Center at Parongpong. The population is all mothers who have toddlers aged 1-5 years, using a random sampling proportion of 49 respondents with univariate and bivariate analysis. The results of this study indicate that there are 22.4% of children under five with abnormal nutritional status, 28.6%. In the parenting style variable, there were 10.2% of the respondents who had a poor parenting style, in the food intake variable, there were 34.7% of the respondents who had a poor food intake. The results of the analysis show that there is a significant relationship between parenting style and food intake with the nutritional status of toddlers. Based on the results of the research, it is hoped that midwives in the working area in primary Health Center at Parongpong will provide health education about parenting and food intake as well as follow up on clinical examinations and refer to higher institutions for toddlers with abnormal nutritional status.